Accumulation of T-cell-suppressive PD-L1 high extracellular vesicles is associated with GvHD and might impact GvL efficacy - Baur, Rebecca; Karl, Franziska; Böttcher-Loschinski, Romy; Stoll, Andrej; Völkl, Simon; Gießl, Andreas; Flamann, Cindy; Bruns, Heiko; Schlötzer-Schrehardt, Ursula; Böttcher, Martin; Schewe, Denis M.; Fischer, Thomas; et al. (Journal for ImmunoTherapy of Cancer, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) represents the only curative treatment option for a number of hemato-oncological disorders. In fact, allo-HSCT is considered as one of the most successful immunotherapies as its clinical efficacy is based on the donor T-cells' capacity to control residual disease. This process is known as the graft-versus-leukemia (GvL) reaction. However, alloreactive T-cells can also recognize the host as foreign and trigger a systemic potentially life-threatening inflammatory disorder termed graft-versus-host disease (GvHD). A better understanding of the underlying mechanisms that lead to GvHD or disease relapse could help us to improve efficacy and safety of allo-HSCT. In recent years, extracellular vesicles (EVs) have emerged as critical components of intercellular crosstalk. Cancer-associated EVs that express the immune checkpoint molecule programmed death-ligand 1 (PD-L1) can suppress T-cell responses and thus contribute to immune escape. At the same time, it has been observed that inflammation triggers PD-L1 expression as part of a negative feedback network. Here, we investigated whether circulating EVs following allo-HSCT express PD-L1 and tested their efficacy to suppress the ability of (autologous) T-cells to effectively target AML blasts. Finally, we assessed the link between PD-L1 levels on EVs to (T-)cell reconstitution, GvHD, and disease relapse. We were able to detect PD-L1 + EVs that reached a peak PD-L1 expression at 6 weeks post allo-HSCT. Development of acute GvHD was linked to the emergence of PD-L1 high EVs following allo-HSCT. Moreover, PD-L1 levels correlated positively with GvHD grade and declined (only) on successful therapeutic intervention. T-cell-inhibitory capacity was higher in PD-L1 high EVs as compared with their PD-L1 low counterparts and could be antagonized using PD-L1/PD-1 blocking antibodies. Abundance of T-cell-suppressive PD-L1 high EVs appears to also impact GvL efficacy as patients were at higher risk for relapse. Finally, patients of PD-L1 high cohort displayed a reduced overall survival.Taken together, we show that PD-L1-expressing EVs are present following allo-HSCT. PD-L1 levels on EVs correlate with their ability to suppress T-cells and the occurrence of GvHD. The latter observation may indicate a negative feedback mechanism to control inflammatory (GvHD) activity. This intrinsic immunosuppression could subsequently promote disease relapse.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Immune Evation; T-Lymphocytes; Transplantation Immunology

Alterations of Immune Cells By Large B Cell Lymphoma Persist Years after Achieving Complete Remission and Correlate with Impaired Adaptive Immunity - Pelzl, Richard; Kübel, Sabrina; Klein, Paulina; Gsottberger, Franziska; Wendland, Kerstin; Petkovic, Srdjan; Brueckl, Valeska; Baur, Rebecca; Völkl, Simon; Mackensen, Andreas; Nganou-Makamdop, Krystelle; Müller, Fabian (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

CD19 CAR-T cell treatment of CNS relapse of Burkitt's lymphoma: A case report - Aigner, Michael; Jacobs, Benedikt; Gary, Regina; Kretschmann, S.; Achenbach, Susanne; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Impact of Nrf2 expression in reconstituting T-cells of allogeneic hematopoietic stem cell transplanted patients - Karl, Franziska; Stoll, Andrej; Böttcher-Loschinski, Romy; Böttcher, Martin; Jacobs, Benedikt; Jitschin, Regina; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (Leukemia, 2020)
CRIS-Team Scopus Importer:2020-07-31

Invariant Natural Killer T Cells from Donor Lymphocyte Infusions (DLI-iNKTs) Contribute to Anti-Tumor Immunity after Allogeneic Hematopoietic Cell Transplantation - Jahnke, Simona; Schmid, Hannes; Secker, Kathy-Ann; Duerr-Stoerzer, Silke; Keppeler, Hildegard; Schumm, Michael; Handgretinger, Rupert; Bethge, Wolfgang; Kanz, Lothar; Schneidawind, Corina; Schneidawind, Dominik; Baur, Rebecca (BLOOD, 2018)
CRIS-Team WoS Importer:2019-02-27

Invariant NKT Cells From Donor Lymphocyte Infusions (DLI-iNKTs) Promote ex vivo Lysis of Leukemic Blasts in a CD1d-Dependent Manner - Jahnke, Simona; Schmid, Hannes; Secker, Kathy-Ann; Einhaus, Jakob; Duerr-Stoerzer, Silke; Keppeler, Hildegard; Schober-Melms, Irmtraud; Schumm, Michael; Handgretinger, Rupert; Bethge, Wolfgang; Kanz, Lothar; Schneidawind, Corina; et al. (Frontiers in Immunology, 2019)
Allogeneic hematopoietic cell transplantation (allo-HCT) is a curative treatment option for hematologic malignancies but relapse remains the most common cause of death. Infusion of donor lymphocytes (DLIs) can induce remission and prolong survival by exerting graft-vs.-leukemia (GVL) effects. However, sufficient tumor control cannot be established in all patients and occurrence of graft-vs.-host disease (GVHD) prevents further dose escalation. Previous data indicate that invariant natural killer T (iNKT) cells promote anti-tumor immunity without exacerbating GVHD. In the present study we investigated lysis of leukemic blasts through iNKT cells from donor-derived lymphocytes for leukemia control and found that iNKT cells constitute about 0.12% of cryopreserved donor T cells. Therefore, we established a 2-week cell culture protocol allowing for a robust expansion of iNKT cells from cryopreserved DLIs (DLI-iNKTs) that can be used for further preclinical and clinical applications. Such DLI-iNKTs efficiently lysed leukemia cell lines and primary patient AML blasts ex vivo in a dose- and CD1d-dependent manner. Furthermore, expression of CD1d on target cells was required to release proinflammatory cytokines and proapoptotic effector molecules. Our results suggest that iNKT cells from donor-derived lymphocytes are involved in anti-tumor immunity after allo-HCT and therefore may reduce the risk of relapse and improve progression-free and overall survival.
CRIS-Team WoS Importer:2019-07-23

Leukemia control after allogeneic hematopoietic cell transplantation through ex vivo expanded invariant natural killer T cells from donor lymphocyte infusions (DLI-INKTS) - Jahnke, Simona; Schmid, Hannes; Secker, Kathy-Ann; Duerr-Stoerzer, Silke; Keppeler, Hildegard; Schumm, Michael; Handgretinger, Rupert; Bethge, Wolfgang; Kanz, Lothar; Schneidawind, Corina; Schneidawind, Dominik; Baur, Rebecca (BONE MARROW TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-10-11

Linking Immunoevasion and Metabolic Reprogramming in B-Cell–Derived Lymphomas - Böttcher, Martin; Stoll, Andrej; Mackensen, Andreas; Mougiakakos, Dimitrios; Baur, Rebecca (Frontiers in Oncology, 2020)
Lymphomas represent a diverse group of malignancies that emerge from lymphocytes. Despite improvements in diagnosis and treatment of lymphomas of B-cell origin, relapsed and refractory disease represents an unmet clinical need. Therefore, it is of utmost importance to better understand the lymphomas’ intrinsic features as well as the interactions with their cellular microenvironment for developing novel therapeutic strategies. In fact, the role of immune-based approaches is steadily increasing and involves amongst others the use of monoclonal antibodies against tumor antigens, inhibitors of immunological checkpoints, and even genetically modified T-cells. Metabolic reprogramming and immune escape both represent well established cancer hallmarks. Tumor metabolism as introduced by Otto Warburg in the early 20th century promotes survival, proliferation, and therapeutic resistance. Simultaneously, malignant cells employ a plethora of mechanisms to evade immune surveillance. Increasing evidence suggests that metabolic reprogramming does not only confer cell intrinsic growth and survival advantages to tumor cells but also impacts local as well as systemic anti-tumor immunity. Tumor and immune cells compete over nutrients such as carbohydrates or amino acids that are critical for the immune cell function. Moreover, skewed metabolic pathways in malignant cells can result in abundant production and release of bioactive metabolites such as lactic acid, kynurenine or reactive oxygen species (ROS) that affect immune cell fitness and function. This “metabolic re-modeling” of the tumor microenvironment shifts anti-tumor immune reactivity toward tolerance. Here, we will review molecular events leading to metabolic alterations in B-cell lymphomas and their impact on anti-tumor immunity.
CRIS-Team Scopus Importer:2020-11-27
Keywords: B-cell-derived Non-Hodgkin lymphoma; chronic lymphocytic leukemia; immune escape; immune therapeutics; metabolism

Palmitoylated Proteins on AML-Derived Extracellular Vesicles Promote Myeloid-Derived Suppressor Cell Differentiation via TLR2/Akt/mTOR Signaling - Tohumeken, Sehmus; Böttcher, Martin; Stoll, Andrej; Loschinski, Romy; Panagiotidis, Konstantinos; Braun, Martina; Saul, Domenica; Baur, Andreas; Bruns, Heiko; Mackensen, Andreas; Jitschin, Regina; Mougiakakos, Dimitrios; et al. (Cancer Research, 2020)
Acute myeloid leukemia (AML) represents the most common acute leukemia among adults. Despite recent progress in diagnosis and treatment, long-term outcome remains unsatisfactory. The success of allogeneic stem cell transplantation underscores the immunoresponsive nature of AML, creating the basis for further exploiting immunotherapies. However, emerging evidence suggests that AML, similar to other malignant entities, employs a variety of mechanisms to evade immunosurveillance. In light of this, T-cell inhibitory myeloid-derived suppressor cells (MDSC) are gaining interest as key facilitators of immunoescape. Accumulation of CD14(+) HLA-DRlow monocyticMDSCs has been described in newly diagnosed AML patients, and deciphering the underlying mechanisms could help to improve anti-AML immunity. Here, we report that conventional monocytes readily takeup AML-derived extracellular vesicles (EV) and subsequently undergo MDSC differentiation. They acquired an CD14(+)HLA-DRlow phenotype, expressed the immunomodulatory indoleamine-2,3-dioxygenase, and upregulated expression of genes characteristic for MDSCs, such as S100A8/9 and cEBP beta. The Akt/mTOR pathway played a critical role in the AML-EV-induced phenotypical and functional transition of monocytes. Generated MDSCs displayed a glycolytic switch, which rendered them more susceptible toward glycolytic inhibitors. Furthermore, palmitoylated proteins on the AML-EV surface activated Toll-like receptor 2 as the initiating event of Akt/mTOR-dependent induction of MDSC. Therefore, targeting protein palmitoylation in AML blasts could block MDSC accumulation to improve immune responses.
CRIS-Team WoS Importer:2020-09-25

Profiling extracellular vesicles (EV) in patients with acute GvHD after allogeneic stem cell transplantation - Böttcher, Martin; Stoll, Andrej; Böttcher-Loschinski, Romy; Rösler, Wolf; Winkler, Julia; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Thrombopoietin receptor agonists for acquired thrombocytopenia following anti-CD19 CAR-T-cell therapy: A case report - Jitschin, Regina; Kharboutli, Soraya; Stoll, Andrej; Büttner-Herold, Maike; Schmidt, Daniela; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (Journal for ImmunoTherapy of Cancer, 2021)
Chimeric antigen receptor (CAR)-modified T-cells targeting CD19 represent a promising therapy for relapsed or refractory (r/r) lymphoma and leukemia. The most common adverse events are immune related and include cytokine release syndrome and neurotoxicity. However, early and late hematological toxicity has emerged as a substantial clinical hurdle leading among others to an increased risk for infections or bleeding. The underlying pathophysiology remains elusive and supportive measures comprise stem cell support or the use of growth factors. Here, we report a 66-year-old woman with r/r diffuse large B-cell lymphoma that received anti-CD19 CAR-T-cells achieving a complete metabolic remission. At month 3 after adoptive cell transfer, the patient still exhibited a grade 3 anemia and a grade 4 thrombocytopenia. The latter required regular platelet transfusions. Bone marrow smear revealed hypocellularity without dysplasia. Despite reduced megakaryopoiesis, immature platelet fraction was elevated indicating an at least partially consumptive underlying component. Based on the successful use of Romiplostim, a thrombopoietin receptor-agonist, in aplastic anemia and immune thrombocytopenia, we treated our patient accordingly. Platelet count (and hemoglobin levels) increased and the patient remains transfusion-free. Taken together, our therapeutic approach could represent a novel strategy for managing CAR-T-cell-related hematotoxicity but, self-evidently, requires further controlled clinical studies.
CRIS-Team Scopus Importer:2021-07-30
Keywords: adoptive; chimeric antigen; hematologic neoplasms; immunotherapy; receptors

Two cases of carfilzomib-induced thrombotic microangiopathy successfully treated with Eculizumab in multiple myeloma - Rassner, Michael; Waesch, Ralph; Schiffer, Mario; Schneider, Johanna; Mackensen, Andreas; Engelhardt, Monika; Baur, Rebecca (BMC Nephrology, 2021)
Background Treatment with proteasome inhibitors like carfilzomib in patients with multiple myeloma (MM) can induce thrombotic microangiopathy (TMA) characterized by neurological symptoms, acute kidney injury, hemolysis and thrombocytopenia. Successful treatment with the monoclonal antibody eculizumab was described for these patients, but reports of ideal management and definitive treatment protocols are lacking. Case Presentation The first case describes a 43-years-old IgG-kappa-MM patient that developed TMA during the first course of carfilzomib-lenalidomide-dexamethasone (KRd) consolidation after autologous stem cell transplantation (ASCT). In the second case, a 59-years-old IgG-kappa-MM patient showed late-onset TMA during the fourth and last cycle of elotuzumab-KRd consolidation within the DSMM XVII study of the German study group MM (DSMM; clinicalTrials.gov Identifier: NCT03948035). Concurrently, he suffered from influenza A/B infection. Both patients had a high TMA-index for a poor prognosis of TMA. Therapeutically, in both patients plasma exchange (TPE) was initiated as soon as TMA was diagnosed. In patient #1, dialysis became necessary. For both patients, only when the complement inhibitor eculizumab was administered, kidney function and blood values impressively improved. Conclusion In this small case series, two patients with MM developed TMA due to carfilzomib treatment (CFZ-TMA), the second patient as a late-onset form. Even though TMA could have been elicited by influenza in the second patient and occurred after ASCT in both patients, with cases of TMA post-transplantation in MM being described, a relation of TMA and carfilzomib treatment was most likely. In both patients, treatment with eculizumab over two months efficiently treated TMA without recurrence and with both patients remaining responsive months after TMA onset. Taken together, we describe two cases of TMA in MM patients on carfilzomib-combination treatment, showing similar courses of this severe adverse reaction, with good responses to two months of eculizumab treatment.
CRIS-Team WoS Importer:2021-02-12